Effects of some Stress Factors (Aluminum, Cadmium and Drought) on Stomata of Roman Nettle (Urtica pilulifera L.) - (:unkn) unknown (UNIV AGR SCI & VETERINARY MED CLUJ-NAPOCA, 2009)
In this study, Roman nettle (Urtica pilulifera L.) seedlings grown sin. different levels of aluminium and cadmium (100 mu M and 200 M) and water stress (moderate and severe stress) treatments. Measurements of stomatal perimeters, diameters and areas from the epidermal sections in lower surfaces of young expanded leaves of main stem and first lateral branches were examined by image processing and analysis software. The data proved that all stomata were affected significantly, but with varying responses, in all treated plants compared to control plants. Excluding severe water stress (WS 2), the data from first lateral branch leaves showed slight sensitivity to all stress treatments. Nevertheless, there were no statistically significant differences between stomatal measurements from main stem and first lateral branch leaves. Particularly, reduction in stomatal diameters of both main stem and first lateral branches in severe water stressed plaints, reducing by 26.45% and 48.09%, respectively; suggest that this could be a response of U. pilulifera to drier environments.
Keywords: Stomata; Al; Cd; water stress; drought; nettle; Urtica pilulifera L.; DETACHED WHEAT LEAVES; WATER-STRESS; CO2 ASSIMILATION; FIELD CONDITIONS; HIGHER-PLANTS; K+ CHANNELS; GROWTH; TOXICITY; TOLERANCE; METABOLISM